AI solution to economic dispatch - Nur Farhanah, Wakiman (2009)
In this study, proposes an AI optimization method for solving the economic dispatch (ED) problem in power systems. Many nonlinear characteristics of the generator, such as ramp rate limits, prohibited operating zone, and non-smooth cost functions are considered using the proposed method in practical generator operation. The feasibility of the proposed method is demonstrated for two different systems, and it is compared with the Conventional method in terms of the solution quality and computation efficiency. The experimental results show that the proposed PSO method was indeed capable of obtaining higher quality solutions efficiently in ED problems.